1986
DOI: 10.1182/blood.v67.6.1560.bloodjournal6761560
|View full text |Cite
|
Sign up to set email alerts
|

Carrier detection in hemophilia A: a cooperative international study. II. The efficacy of a universal discriminant

Abstract: Factor VIII (F.VIII) and von Willebrand factor (VWF):Ag data collected by eight laboratories on a total of 336 obligatory carriers of hemophilia A and 137 normal women were used to answer several questions concerning the construction of linear discriminants for carrier detection. It was found: that a “universal” linear discriminant can be constructed which is suitable for use in all laboratories and is nearly as effective as laboratory-specific discriminants; that inclusion of age and ABO blood type data impro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
2

Year Published

1987
1987
2003
2003

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 0 publications
0
8
0
2
Order By: Relevance
“…It was concluded that in these 10 families a mutation had occurred either in the grandfather's or mother's germ cell. To ascertain in which generation the mutation had occurred, VIII : C and vWF concentrations were determined in the mothers of the hemophiliacs in these 10 families, and the odds on maternal carriership estimated by linear discriminant analysis (16). Of these 10 mothers, four had odds of > 104: 1 for carriership, two for non-carriership (odds t0.025: I), i.e., the mutation had probably occurred in the mother's germ cell, and four were indeterminate.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was concluded that in these 10 families a mutation had occurred either in the grandfather's or mother's germ cell. To ascertain in which generation the mutation had occurred, VIII : C and vWF concentrations were determined in the mothers of the hemophiliacs in these 10 families, and the odds on maternal carriership estimated by linear discriminant analysis (16). Of these 10 mothers, four had odds of > 104: 1 for carriership, two for non-carriership (odds t0.025: I), i.e., the mutation had probably occurred in the mother's germ cell, and four were indeterminate.…”
Section: Resultsmentioning
confidence: 99%
“…St 14 (kindly provided by Dr J.-L. Mandel, Inserm, Strasbourg), which after digestion with Taq 1 detects an extragenic polymorphic system with 10 alleles (1 1).Statistics. The odds for carriership based on concentrations of VII1:C and wWF were estimated with linear discriminant analysis as perGreen et al (1986).…”
mentioning
confidence: 99%
“…5 Accuracy in the assessment of the probability of carriership can be enhanced by using a program for computer analysis of data for laboratory variables. 6 The combined use of pedigree and laboratory data will only yield a probability of carriership, even if it is often very strong.…”
Section: Basic Analysis Of the Potential Carriermentioning
confidence: 99%
“…Nevertheless, between 6 and 20% of women will be misclassified either as normal or as carriers on the basis of these methods. 11,15,[21][22][23] A complementary and highly reliable method for this task has been provided by recombinant DNA technology.…”
Section: Genetics Of Hemophilia Amentioning
confidence: 99%